2017
DOI: 10.1117/1.jbo.22.3.034001
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative characterization of mechanically indented in vivo human skin in adults and infants using optical coherence tomography

Abstract: Quantitative characterization of mechanically indented in vivo human skin in adults and infants using optical coherence tomography," J. Biomed. Opt. 22(3), 034001 (2017), doi: 10.1117/1.JBO.22.3.034001. Abstract. Influenced by both the intrinsic viscoelasticity of the tissue constituents and the time-evolved redistribution of fluid within the tissue, the biomechanical response of skin can reflect not only localized pathology but also systemic physiology of an individual. While clinical diagnosis of skin pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Although there are fairly rigid experimental requirements to perform this work, many tissue types have been explored and characterized 133 136 One example is through the use of a commercial probe that was adapted to detect the biomechanical properties of human skin with aging by observing elasticity and scattering metrics, and was performed in vivo on human subjects 137 . Still, employing elastography techniques in a handheld probe-based system adds considerable difficulty, as the exact experimental and boundary conditions cannot always be guaranteed.…”
Section: Stage 2 Systems: Biological Discovery Through Technical Innomentioning
confidence: 99%
“…Although there are fairly rigid experimental requirements to perform this work, many tissue types have been explored and characterized 133 136 One example is through the use of a commercial probe that was adapted to detect the biomechanical properties of human skin with aging by observing elasticity and scattering metrics, and was performed in vivo on human subjects 137 . Still, employing elastography techniques in a handheld probe-based system adds considerable difficulty, as the exact experimental and boundary conditions cannot always be guaranteed.…”
Section: Stage 2 Systems: Biological Discovery Through Technical Innomentioning
confidence: 99%
“…Similarly, for OCTSS analysis, the changes in the skin tension based on hand positioning may lead to the redistribution of the unbound fluid within the tissue, which could subsequently affect the microstructure detected by the OCTSS. Previous work has demonstrated that the optical properties of skin can be affected by an external mechanical stimulation . Therefore, imaging an area sufficiently far away from movable joints and incorporating an aiming laser with the current setup may enhance the sensitivity and reliability of OCT and OCE to accurately monitor SSc progression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work demonstrated the correlation of OCT‐assessed optical density in the papillary dermis with local mRSS evaluated from the forearm ( r = −.66 to −0.7) and finger ( r = −.55) . Furthermore, tissue structural properties can be quantitatively characterized by various parameters based on the OCT structural images, such as fractal analysis , optical attenuation , and spatial speckle analyses . With the superior spatial resolution of OCT, optical coherence angiography has promising potential to image microangiopathy severity in SSc patients since SSc also has a substantial vasculopathic component .…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, ultrasound, computed tomography (CT), and MRI are currently utilized to guide the placement of RFA probes and evaluate ablation outcomes [49]. With previously demonstrated intraoperative imaging capabilities [50], an OCT-assisted clinical environment is also foreseen, where handheld or catheter-based OCT can be utilized to both detect the local tumor microstructure and/or image the altered mechanical response of tissue through morphological alteration [50][51][52]. By incorporating magnetomotive components into a handheld or catheter-based OCT platform, in situ MM-OCE-based thermal dosage evaluation may be feasible in the future, serving as a physiologically-meaningful and complementary approach for real-time thermal treatment dosimetry.…”
Section: Discussionmentioning
confidence: 99%